Sociabilidad literaria e imprenta: Academias poéticas madrileñas publicadas entre 1661 y 1663: Literary Sociability and the Printing Press : Madrid Poetic Academies Published Between 1661 and 1663 - Osuna, Inmaculada (My University, 2019)
Towards 1650 the formation of poetical academies is a usual practice in several Spanish cities, and especially in Madrid. However, until the second half of the century there are no prints reproducing a specific Academy session, with the speeches of the literary act and the poems on demand. This publishing phenomenon stands out above all in Madrid, although, to a lesser extent, it reaches a few other Spanish cities. The Jardín de Apolo (1654), published by Melchor de Fonseca y Almeida, is ahead of its true emergence, between 1661 and 1663. The article deals with the printed Madrid academies in those three years, taking into account their editorial characteristics, their participants and, in some cases, the signs of a possible restricted diffusion, still close to the habits of the manuscript circulation., Hacia 1650 la conformación de academias poéticas es una práctica usual en varias ciudades españolas, y especialmente en Madrid. Sin embargo, hasta la segunda mitad de siglo no se encuentran impresos que reproducen una sesión concreta de academia, con los discursos del acto literario y los poemas de encargo. Este fenómeno editorial destaca sobre todo en Madrid, aunque, en menor medida, alcanza a otras pocas ciudades españolas. El Jardín de Apolo (1654), publicado por Melchor de Fonseca y Almeida, anticipa su verdadera eclosión, entre 1661 y 1663. El artículo aborda las academias madrileñas impresas de esos tres años, atendiendo a sus características editoriales, sus participantes y, en algunos casos, los indicios sobre una posible circulación restringida, aún próxima a los hábitos del manuscrito.
Keywords: Literary Academies; Sociability; Printing Press; Poetry; Seventeenth Century; Melchor de Fonseca; Madrid; Academias literarias; sociabilidad; imprenta; poesía; siglo XVII; Madrid; Melchor de Fonseca